Center-Periphery Migration in Malaysia: A Spatial Analysis of Non-Citizen Population Growth (1991–2020) Guided by World Systems and Social Network Theory - Rose, Rosniza Aznie Che; Ismail, Muhamad Fadzil (Journal of Posthumanism, 2025)
This study investigates the spatial dynamics of non-citizen labor migration in Peninsular Malaysia from 1991 to 2020, focusing on population growth patterns and structural migration drivers through the lens of World Systems Theory and Social Network Theory. Utilizing census data and spatial analysis in ArcGIS Pro 2.9.0, the study maps a 92 km southwestward shift in the mean center of non-citizen populations, with increasing spatial concentration in Selangor, Kuala Lumpur, and Penang. Hot Spot Analysis and rising Moran’s I values confirm persistent and intensifying spatial clustering. The sharpest population increase occurred in Selangor (+481%), Penang (+365%), and Kuala Lumpur (+278%), underscoring center-periphery migration dynamics. These findings reveal critical regional disparities and the urban concentration of foreign labor, highlighting the urgency for targeted, inclusive policies aligned with SDG 8 and SDG 11. The study offers original insights into migration geography and urban sustainability in Malaysia’s evolving labor landscape.